Perbandingan Aktivitas Enzim Cholinesterase Serum dengan Metode Fotometri Teknik Sample Start dan Substrat Start - Farha Salsabila Widigdo; Rohayati Rohayati; Zuri Rismiarti; Ani Riyani (Akademi Analis Kesehatan Pekalongan, 2024)
Cholinesterase examination related to liver function and carried out by kinetic photometric method with two type reagent addition techniques, namely sample start and substrat start. Both techniques are related to incubation time during examination which affects waiting time for laboratory service result. This study aims to determine comparison of serum cholinesterase activity measured by sample start and substrat start techniques. The research was conducted in May 2024 at Clinical Chemistry Laboratory of Bandung Polytechnic Health. The research using Paired Sample T-test of 30 serum samples measured cholinesterase activity at 405 nm wavelength photometer using sample start and substrat start techniques so that 60 research data were obtained. The result of Paired Sample T-test showed that serum cholinesterase activity with sample start technique had lower trend value than serum cholinesterase activity with substrat start technique and there was no clinical effect with an analytical difference in cholinesterase activity measured by both techniques indicated by the Sig value 0.000 and TE% < TEa% that 4.72% < 8.7%. Therefore, the sample start and substrat start techniques in photometric method of serum cholinesterase activity can be applied for daily testing because the difference in value of two techniques has no clinical effect.